THE ROLE OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN IMPROVING STUDENTS' SOCIAL CONCERN IN MA. WALISONGO GENDING - Futohuddin, Muhammad; Suryanto, Bradhiansyah Tri; Suhermanto, Suhermanto; Holifah, Holifah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Social care is the attitude and behavior of a person or group of people to pay attention, respect, and assist those in need. It involves empathy, concern, and responsibility for the well-being of others. It is essential to form these values from an early age, especially in the younger generation, so that they can provide benefits to society in the future. This research aims to identify the role of Islamic Religious Education (PAI) teachers in increasing students' social awareness at MA Walisongo Gending, especially in fostering a caring attitude towards the surrounding environment and readiness to help other people in need, especially in the context of Islamic education. This research uses a qualitative approach with a case study method, and data is collected through observation, interviews, and documentation. Research confirms that the role of Islamic Religious Education (PAI) teachers is vital in forming students' social awareness. PAI teachers act as educators who teach social values in Islam and as learning resources that provide relevant and in-depth material. They are also role models in social behavior, providing tangible examples of doing good and caring for others. Apart from that, PAI teachers act as motivators who actively encourage students to participate in social activities. They encourage and support students to care about the surrounding environment and do good to others. As mentors and evaluators, PAI teachers provide direction and feedback on students' social activities, guiding them in planning, implementing, and evaluating their social activities.